Analysis of cold tolerance in sorghum [Sorghum bicolor (L.) Moench] - Maulana, Frank (Kansas State University, 2011)
Cold temperature stress is an important abiotic constraint to grain sorghum production in temperate regions. In the United States, low temperature in late spring and early fall has limited sorghum production to a narrow growing period. Deployment of cold tolerance traits may widen this window and hence contribute to increased production. The objectives of this study were (1) to determine the effect of early and mid-season cold temperature stress on growth, phenology and yield components of sorghum, and identify key traits that are most sensitive to cold stress at seedling and flowering stages, and (2) to identify new sources of cold tolerance for use in breeding programs. Series of controlled environment (greenhouse/growth chamber) and field experiments were carried out. Three sorghum genotypes of variable response, Shan Qui Red (tolerant), SRN39 (susceptible) and Pioneer 84G62 (unknown) were subjected to cold (15/13ºC day/night) and normal (25/23ºC day/night) temperature at seedling (Experiment I) and flowering (Experiment II) stages. The genotypes were planted in a greenhouse using a 5L polytainer pots. Each pot consisted of a single plant and each plot was represented by three pots. A split-plot design with three replications was used in both experiments with temperature regimes as main plots and genotypes as sub-plots. Three days after emergence, experiment I plants were moved to the growth chamber and subjected to the designated temperature treatments. For experiment II, the treatments were assigned at heading stage immediately before anthesis had begun. The treatments lasted 10 d in both experiments. Data were collected on seedling characteristics and leaf chlorophyll content in experiment I, days to flowering, maturity, and yield components in both experiments, and anthesis duration in experiment II. For the field experiment, 150 sorghum germplasm collections of potential cold tolerance along with tolerant and susceptible checks were evaluated for emergence and seedling traits under early planting (April 13) at soil temperature of 20.1/13.4 ºC max/min. The normal temperature treatment was applied by planting at regular season (May 26) at soil temperature of 30.0/20.4ºC max/min. Twenty-four genotypes selected based on field emergence and seedling vigor were further screened under controlled environment. Early-season stress significantly reduced leaf chlorophyll content, all seedling traits (height, vigor and dry weight), and also delayed flowering and maturity. But it had no effect on final leaf number, plant height and yield components. Genotypic response to early stress was significant for all traits with the susceptible checks having the lowest score for all seedling traits. Mid-season cold stress prolonged anthesis duration, delayed maturity and highly reduced all yield components. Several genotypes among the 150 had higher seedling vigor and emergence than the tolerant check, Shan Qui Red. In conclusion, reduced seedling vigor as a result of early stress had no effect on final yield provided that stand establishment was not compromised while mid season stress is damaging to yield. The wide genetic variation for the traits indicates the potential for improvement of cold tolerance in sorghum.
Keywords: cold stress; Agronomy (0285); Biology, Plant Physiology (0817)